Presentations : sharpen your message, persuade your audience, gauge your impact - Thomas, James Edward (20 minute manager series., 2022)
Feeling stressed about your upcoming presentation? Whether you're nervous about how you'll organize your thoughts or how you'll articulate them on the big day, Presentations provides the quick guidelines and expert tips you need to: - Craft your message - Prepare and rehearse effectively - Engage your audience - Manage Q & A sessions Don't have much time? Get up to speed fast on the most essential business skills with HBR's 20-Minute Manager series. Whether you need a crash course or a brief refresher, each book in the series is a concise, practical primer that will help you brush up on a key management topic. Advice you can quickly listen to and apply, for ambitious professionals and aspiring executives-from the most trusted source in business.